Assessing the Influence of ENSO on Monthly Rainfall in Samarinda City (1994–2024) - Wibowo, Ragantar Nur; Ramadhan, Muhammad Luthfi; Wahyuda, Muhammad; Al-ghifari, Najwan; Budiarsa, Anugrah Aditya (Dept. Marine Science, 2026)
Climate variability, specifically changes in monthly rainfall patterns, increases the risk of hydrometeorological disasters such as flooding and prolonged droughts in Samarinda City, East Kalimantan. This condition is amplified by the El Niño-Southern Oscillation (ENSO) phenomenon, which triggers the El Niño (drought) and La Niña (heavy rainfall) phases. This study analyzes the influence of ENSO on monthly rainfall variability in Samarinda City from 1994 to 2024. Monthly rainfall data were obtained from the Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS), while ENSO conditions were represented by NOAA's Niño 3.4 sea surface temperature (SST) anomaly index. The analytical methods included time-series comparison, Pearson correlation analysis, ENSO phase classification based on a ±0.5°C threshold, and composite spatial analysis to map average rainfall distribution across El Niño, Neutral, and La Niña phases. The results demonstrate a statistically significant negative correlation between the Niño 3.4 index and monthly rainfall (r = -0.450; p = 6.38 × 10⁻²⁰). This indicates that rainfall in Samarinda tends to decrease significantly during El Niño conditions and increase during La Niña conditions. The coefficient of determination (R² = 0.202) reveals that ENSO accounts for approximately 20.2% of monthly rainfall variability, while the remaining 79.8% is influenced by other regional and seasonal climatic factors. These findings confirm that ENSO is a key climatic factor for improving risk assessment and hydrometeorological disaster mitigation in Samarinda City.